(untitled) (Лучшие интеллектуальные исследования, 2025)
ANNOTATION: This article explores the role of language and literature in shaping an individual’s personality, social consciousness, and moral values. Special attention is given to the influence of Uzbek literature and language on the upbringing of the younger generation, as well as to the significance of literature as a spiritual and educational force.